2020
DOI: 10.1038/s41467-020-18104-5
|View full text |Cite
|
Sign up to set email alerts
|

Cyst growth in ADPKD is prevented by pharmacological and genetic inhibition of TMEM16A in vivo

Abstract: In autosomal dominant polycystic kidney disease (ADPKD) multiple bilateral renal cysts gradually enlarge, leading to a decline in renal function. Transepithelial chloride secretion through cystic fibrosis transmembrane conductance regulator (CFTR) and TMEM16A (anoctamin 1) are known to drive cyst enlargement. Here we demonstrate that loss of Pkd1 increased expression of TMEM16A and CFTR and Cl − secretion in murine kidneys, with TMEM16A essentially contributing to cyst growth. Upregulated TMEM16A enhanced intr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(85 citation statements)
references
References 47 publications
9
70
0
Order By: Relevance
“…The KspCreERT2;Pkd1lox;lox system was used to obtain a tamoxifen inducible tubule-specific knockout of Pkd1, as described previously [ 24 , 33 ]. Knockdown of Pkd1 in male and female mice was validated by RT-PCR ( Figure 1 A,B).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The KspCreERT2;Pkd1lox;lox system was used to obtain a tamoxifen inducible tubule-specific knockout of Pkd1, as described previously [ 24 , 33 ]. Knockdown of Pkd1 in male and female mice was validated by RT-PCR ( Figure 1 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study we reported a crucial role of the Ca 2+ -activated Cl − channel TMEM16A for the development of polycystic kidneys in Pkd1 −/− mice and in additional in vitro models for ADPKD [ 20 , 23 , 24 ]. We therefore expected to find higher levels of TMEM16A-expression in kidneys from male Pkd1 −/− mice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations